Pulmonary artery banding: a 20-year experience at a tertiary care center in a developing country - Ghoussaini, Racha; Zareef, Rana; Makarem, Adham; Younis, Nour; Al Hassan, Sally; El Rassi, Issam; Obeid, Munir; Bitar, Fadi; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2024)
Aim Pulmonary artery banding serves as an important palliative procedure used for the management of several congenital heart lesions. This study aims to describe a 20-year experience of pulmonary artery banding at a tertiary care center in a developing country. Methods This is a retrospective chart review of patients who underwent pulmonary artery banding over a 20-year period between January 2000 and July 2020 in a tertiary care center in a developing country. Data regarding demographics, indications, diagnosis, echocardiographic findings, postoperative complications, hospital stay, and outcomes were recorded. Results A total of 143 patients underwent pulmonary artery banding between 2000 and 2020, with a decrease from approximately 15 surgeries per year in 2012 to 1–2 surgeries a year in 2020. At the time of banding, the median age of patients was approximately 90 days [interquartile range, IQR, 30–150 days]. Four patients (2.8%) died during the band placement. No significant association was observed between baseline characteristics or type of heart defect at presentation and postoperative morbidity and mortality. Conclusion Pulmonary artery banding remains useful in a subset of congenital heart lesions and as a surgical palliation, with relatively low mortality, allowing postponement of total correction to a higher weight. This technique continues to be valuable in developing countries or for heart surgical programs with limited resources.